Home sweet home? Adjustments in the ecology, behaviour and vocalisations of Amazonian squirrel monkeys inhabiting an Atlantic forest fragment. Issue 2 (4th March 2019) - Campêlo, Anielise C.; Souza-Alves, João P.; Lima, Ingrid M. Silva de; Araújo, Ana C. Lima; Oliveira-Silva, Liany R. Bezerra; Bezerra, Bruna
Abstract : Inadvertent or intentional introductions of species in non-native habitats are forcing them to adapt quickly, resulting in evolutionarily significant changes in their ecology and social organisation. Understanding how these species are adapting in non-native areas will elucidate evolutionary aspects of migration and adaptation skills of exotic species in general. Thus, we investigated how Amazonian squirrel monkeys ( Saimiri sciureus ) have adjusted their behavioural ecology and call propagation in an Atlantic forest fragment in north-eastern Brazil. Behavioural ecology data were obtained via instantaneous scan and ad libitum sampling methods. Call propagation data were obtained through playback experiments conducted in the Atlantic and Amazon forests. Atlantic forest squirrel monkey diet was found to be composed, primarily, of fruits considered "exotic" to the region. There was no variation between dry and wet months in food-resource exploitation except for flowers. Squirrel monkeys spent most of their time engaged in locomotion and foraging activities and had a preference for the Atlantic forest mid-strata. Nevertheless, resting, locomotion and social activities were most frequently demonstrated in the dry months, whereas foraging behaviours were mostly performed in the wet months. We found no variation between dry and wet months in the vertical use of the stratum, daily path length or home range size. The propagation of squirrel monkey isolation calls was more efficient in the Amazon compared with the Atlantic forest, with call acoustic parameters degrading faster in the Atlantic forest. Our results indicate that exotic squirrel monkeys have adjusted their activity pattern and diet in the Atlantic forest, resulting in behavioural variations consistent with the existing resources. Vocalisations, however, despite not being fully adapted for propagation in the Atlantic forest, do not appear to interfere in the occupation success of the species in the Atlantic forest.